Outcomes Associated With the Nationwide Introduction of Rapid Response Systems in The Netherlands*. Issue 12 (December 2015) - Ludikhuize, Jeroen; Brunsveld-Reinders, Anja H.; Dijkgraaf, Marcel G. W.; Smorenburg, Susanne M.; de Rooij, Sophia E. J. A.; Adams, Rob; de Maaijer, Paul F.; Fikkers, Bernard G.; Tangkau, Peter; de Jonge, Evert
Abstract : Objective: To describe the effect of implementation of a rapid response system on the composite endpoint of cardiopulmonary arrest, unplanned ICU admission, or death. Design: Pragmatic prospective Dutch multicenter before-after trial, Cost and Outcomes analysis of Medical Emergency Teams trial. Setting: Twelve hospitals participated, each including two surgical and two nonsurgical wards between April 2009 and November 2011. The Modified Early Warning Score and Situation-Background-Assessment-Recommendation instruments were implemented over 7 months. The rapid response team was then implemented during the following 17 months. The effects of implementing the rapid response team were measured in the last 5 months of this period. Patients: All patients 18 years old and older admitted to the study wards were included. Measurements and Main Results: In total, 166, 569 patients were included in the study representing 1, 031, 172 hospital admission days. No differences were observed in patient demographics between periods. The composite endpoint of cardiopulmonary arrest, unplanned ICU admission, or death per 1, 000 admissions was significantly reduced in the rapid response team versus the before phase (adjusted odds ratio, 0.847; 95% CI, 0.725–0.989; p = 0.036). Cardiopulmonary arrests and in-hospital mortality were also significantly reduced (odds ratio, 0.607; 95% CI, 0.393–0.937; p = 0.018 and odds ratio, 0.802; 95% CI, 0.644–1.0; p = 0.05, respectively). Unplanned ICU admissions showed a declining trend (odds ratio, 0.878; 95% CI, 0.755–1.021; p = 0.092), whereas severity of illness at the moment of ICU admission was not different between periods. Conclusions: In this study, introduction of nationwide implementation of rapid response systems was associated with a decrease in the composite endpoint of cardiopulmonary arrests, unplanned ICU admissions, and mortality in patients in general hospital wards. These findings support the implementation of rapid response systems in hospitals to reduce severe adverse events. Abstract : Supplemental Digital Content is available in the text.